Differentiated Instruction in Inclusive Classrooms: Teacher Preparedness and Student Learning Outcomes in Primary Education - Annisa Nur Wahyuningsih; Desi Nurillah; Monica Roito Ambarita; Virzha Aulianna Dhaksietsatsura; Ayu Fajarwati (International Journal of Educational Research Excellence (IJERE), 2026)
This study investigates primary school teachers’ preparedness to implement differentiated instruction (DI) in inclusive classrooms and its relationship with student learning outcomes in the Indonesian context. A quantitative cross‑sectional survey was conducted with 287 classroom teachers from 34 public and private inclusive primary schools in Yogyakarta and Central Java. Teacher preparedness was measured using a four‑dimensional scale (knowledge, skills, attitudes, self‑efficacy), while student outcomes were operationalized as class‑aggregate academic achievement and engagement. Data were analysed through descriptive statistics, Pearson correlations, multiple regression, and ANOVA. Overall teacher preparedness was moderate (M=3.72, SD=0.68), with the lowest dimension being knowledge of DI (M=3.24). A significant positive correlation was found between teacher preparedness and student academic outcomes (r=0.47, p<.001) and engagement (r=0.53, p<.001). Multiple regression revealed that self‑efficacy (β=0.34) and pedagogical skills (β=0.28) were the strongest predictors of academic achievement, while attitudes (β=0.29) and self‑efficacy (β=0.25) predicted engagement. Teachers who had participated in formal DI training demonstrated significantly higher preparedness (t=6.89, p<.001), and years of experience positively moderated the relationship. Teacher preparedness for DI is a critical determinant of student success in inclusive primary classrooms. Strengthening pre‑service and in‑service training that targets self‑efficacy and concrete DI skills is urgently recommended to enhance inclusive education quality in Indonesia